GE_GERICHTE P/843/2014 vom 9. Juni 2015 - GE Cour de justice (2015)
RETRAIT(VOIE DE DROIT); INDEMNITÉ(EN GÉNÉRAL) | CP.33.1; CP.33.2; CP.33.4; CPP.386.2; CPP.429.1.a; CPP.432.2; CPP.426.2; CPP.427.2.a